Skeptic Spirituality or the Accidental Buddhism of Machado de Assis's O Segredo do Bonzo - Dilip Loundo; Teresinha Vânia Zimbrão da Silva (Horizonte, 2014)
The objective of the present article is to support the idea that Machado de Assis’ work conforms well to what may be called a non-religious spirituality. For that, the article’s main focus is the analysis of the short story “O Segredo do Bonzo: Capítulo Inédito de Fernão Mendes Pinto”, published in 1882’s collection titled Papéis Avulsos, where the main principles of that spirituality, which is spread all over his work,  are given in a nutshell. In a first moment, we analise the intertextuality between Machado’s short story “O Segredo do Bonzo” and Portuguese Renaissance writer’s travelogue Peregrinação and the Machado’s nineteen century critique of the west’s main universalizing proposals: Christianity, scientificity and Enlightenment. In a second moment, we analise the philosophical implications of the primacy given to ‘opinion’ as an existential foundation and as a constitutive element of reality, in a context of close proximity with the soteriological traditions of ancient Greek skepticism, on the one hand, and Buddhism, on the other. A critic of religion, specially of Christian religion, Machado’s  ‘accidental’ association with Buddhism is symptomatic of a very peculiar form of non-religious spirituality.